Triply periodic minimal surface porous implants to reconstruct bone defects - Verma R.; Singh N.K.; Rai S.K.; Kumta S. (My University, 2025)
Bone defects are serious complications that occur by trauma, tumor, infection, or pathological disorders. In the present scenario, researchers are paying attention to research into possibilities of healing large segmental bone defects by implantation of lightweight implants. Porous design of implants manages the upsides of minimizing stress shielding and improving the bone ingrowth and minimizing relative micromotion between the implant and surrounding tissue. This paper presents the implant architecture with triply periodic minimal surface (TPMS) gyroid based unit cell to analyze the effect of gradient elastic moduli and compressive strength as a function of porosity. TPMS gyroid cells were developed with seven levels of porosity by retrieving mathematical expressions and computer-aided design packages. These modeled structures were submitted to finite element analysis for static loading, compressive strength based on von-mises criteria to determine the deformation behavior and to estimate the effective moduli. Results indicate that the deformation induced by body weight is highly dependent on the pore size and distribution. Further, it is also evident that TPMS can reduce the effective modulus and implant weight by 75-80%. Based on the results and their comparisons on available literature on deformation and elastic moduli, the developed TPMS gyroid structure that effectively mimics the mechanical properties of cancellous bone has been identified. © 2020 Elsevier Inc. All rights reserved.